Analisa Strategis Kesiapan Operasional TNI Angkatan Laut dalam Menghadapi Dinamika Lingkungan Maritim - Rizanny Nurdiansyah, Dickry (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Indonesia, as the largest archipelagic nation globally, faces significant strategic challenges in its maritime domain. The Indonesian Navy's preparedness is paramount in safeguarding the nation's interests amid evolving geopolitical dynamics, resource competition, and maritime security threats such as piracy and terrorism. This paper examines the role and importance of the Operational Ready Force (ORF) within Indonesia's maritime defence strategy. By employing strategic analysis, the study evaluates the Navy's operational readiness, focusing on resource allocation, technological advancements, and international cooperation necessary to enhance the ORF's effectiveness. The research utilizes a comprehensive methodology, including literature review, official documents, and expert interviews, to provide an in-depth understanding of the Indonesian Navy's readiness to address dynamic maritime environments. The paper also explores the strategic implications of global, regional, and national maritime developments, emphasizing the necessity for an adaptive and resilient maritime strategy. The findings suggest that ORF is crucial in bolstering the Indonesian Navy's capabilities, enabling rapid and effective responses to maritime threats while protecting national sovereignty. The study concludes with recommendations for further development of ORF, ensuring Indonesia's continued maritime security and regional stability through integrated technology, strengthened international collaboration, and adaptive threat response strategies.